Sustainability Analysis of "Boat Class" Service Innovation in Pangkajene Islands District - Rasmiati Tahir; Sangakala Sangakala; Suryadi Lambali; Hasniati Hasniati (Journal La Sociale, 2023)
The availability of legitimacy and support from the government is the strength of the sustainability of a public service innovation. Research design. This type of qualitative research is descriptive with a case study method. Population and Sample. The location of this research is in Pangkep Regency. On two pilot islands, the Boat Class project, Salemo and Sakuala, in North Liukang Tupabbiring District, Mattiro Bombang Village. Data sources come from three things: interviews with informants who are representative or who are directly involved with the innovation of the Boat Class, direct observation of the island, and a number of relevant documents. Instruments. We use in-depth interview guidelines in a structured and unstructured manner. Procedures. Data analysis using interactive methods based on the Miles and Huberman model. Research questions. What is the sustainability of the Boat Class in terms of regulation and replication? And, what are the stages of formulating the rule? Result and conclusions. The Boat Class already has three key laws in its future expansion. The Boat class has replicated four adopter units. An international institution, KOMPAK Australia, assisted in the formulation of Boat Class regulations.